5H-Benzo[d]Benzo[4,5]Imidazo[2,1-b][1,3]Thiazine as a Novel Electron-Acceptor Cored High Triplet Energy Bipolar Host Material for Efficient Solution-Processable Thermally Activated Delayed Fluorescence Organic Light-Emitting Diodes - Godumala, Mallesham; Yoon, Jiwon; Park, Seo Yeon; Lee, Chiho; Kim, Youngseo; Jeong, Ji-Eun; Park, Sungnam; Woo, Han Young; Cho, Min Ju; Choi, Dong Hoon (Frontiers in Chemistry, 2020)
Organic entities that can transport electrons are seldom available to develop adequate bipolar host materials applicable for solution-processable thermally activated delayed fluorescence (TADF)-organic light-emitting diodes (OLEDs). Therefore, the introduction of new electron-affine entities that plausibly demonstrate high triplet energy (ET) is of urgent need. In this contribution, we introduced benzimidazo[1,2-a][3,1]benzothiazine (BBIT) as a novel electron-affine entity and developed two new bipolar host materials, CzBBIT and 2CzBBIT. Both host materials exhibit high ET of 3.0 eV, superior thermal robustness with the thermal decomposition temperature of up to 392 °C, a glass transition temperature of up to 161 °C, and high solubility in common organic solvents. Single-carrier devices evidenced that both the hosts manifest balanced charge-carrier transport properties. Consequently, the solution-processable OLEDs fabricated using a recognized IAcTr-out as the green TADF emitter doped into CzBBIT as the host, realized a maximum external quantum efficiency (EQE) of 23.3%, while the 2CzBBIT: IAcTr-out blend film-based device displayed an EQE of 18.7%. These outcomes corroborated that this work could shed light on the scientific community on the design of new electron-affine entities to establish the effective use of bipolar host materials toward proficient solution-processable TADF-OLEDs.